Oral administration of branched-chain amino acids ameliorates high-fat diet-induced metabolic-associated fatty liver disease via gut microbiota-associated mechanisms - Zhang, Ranran; Mu, Hongna; Li, Ziyun; Zeng, Jie; Zhou, Qi; Li, Hongxia; Wang, Siming; Li, Xianghui; Zhao, Xianghui; Sun, Liang; Chen, Wenxiang; Dong, Jun; et al. (Frontiers in Microbiology, 2022)
Branched-chain amino acids (BCAAs), essential amino acids for the human body, are mainly ob-tained from food. High levels of BCAAs in circulation are considered potential markers of meta-bolic-associated fatty liver disease (MAFLD) in humans. However, there are conflicting reports about the effects of supplement of BCAAs on MAFLD, and research on BCAAs and gut microbiota is not comprehensive. Here, C57BL/6J mice were fed a high-fat diet with or without BCAAs to elucidate the effects of BCAAs on the gut microbiota and metabolic functions in a mouse model of MAFLD. Compared to HFD feeding, BCAA supplementation significantly reduced the mouse body weight, ratio of liver/body weight, hepatic lipid accumulation, serum levels of TC, LDL-C and ALT, and expressions of the lipogenesis-related enzymes Fas, Acc, and Scd-1, and increased expressions of the lipolysis-related enzymes Cpt1A and Atgl in the liver. BCAAs supplementation also coun-teracted HFD-induced elevations in serum BCAAs levels by stimulating the enzymatic activity of BCKDH. Furthermore, BCAAs supplementation markedly improved the gut bacterial diversity and altered the gut microbiota composition and abundances, especially those of genera, in association with MAFLD and BCAAs metabolism. These data suggest that BCAA treatment improves HFD-induced MAFLD through mechanisms involving intestinal microbes.